Barriers and facilitators in using a Clinical Decision Support System for fall risk management for older people: a European survey - Ploegmakers, Kim J; Medlock, Stephanie; Linn, Annemiek J; Lin, Yumin; Seppälä, Lotta J; Petrovic, Mirko; Topinkova, Eva; Ryg, Jesper; Mora, Maria Angeles Caballero; Landi, Francesco; Thaler, Heinrich; Szczerbińska, Katarzyna; et al. (European geriatric medicine, 2022)
PURPOSE: Fall-Risk Increasing Drugs (FRIDs) are an important and modifiable fall-risk factor. A Clinical Decision Support System (CDSS) could support doctors in optimal FRIDs deprescribing. Understanding barriers and facilitators is important for a successful implementation of any CDSS. We conducted a European survey to assess barriers and facilitators to CDSS use and explored differences in their perceptions. METHODS: We examined and compared the relative importance and the occurrence of regional differences of a literature-based list of barriers and facilitators for CDSS usage among physicians treating older fallers from 11 European countries. RESULTS: We surveyed 581 physicians (mean age 44.9 years, 64.5% female, 71.3% geriatricians). The main barriers were technical issues (66%) and indicating a reason before overriding an alert (58%). The main facilitators were a CDSS that is beneficial for patient care (68%) and easy-to-use (64%). We identified regional differences, e.g., expense and legal issues were barriers for significantly more Eastern-European physicians compared to other regions, while training was selected less often as a facilitator by West-European physicians. Some physicians believed that due to the medical complexity of their patients, their own clinical judgement is better than advice from the CDSS. CONCLUSION: When designing a CDSS for Geriatric Medicine, the patient's medical complexity must be addressed whilst maintaining the doctor's decision-making autonomy. For a successful CDSS implementation in Europe, regional differences in barrier perception should be overcome. Equipping a CDSS with prediction models has the potential to provide individualized recommendations for deprescribing FRIDs in older falls patients.
Keywords: Humans; Accidental Falls; Surveys and Questionnaires; mužské pohlaví; řízení rizik; průzkumy a dotazníky; úrazy pádem; Disease Susceptibility; ženské pohlaví; Physicians; náchylnost k nemoci; lékaři; Decision Support Systems, Clinical; lidé; systémy pro podporu klinického rozhodování; Aged; Risk Management; senioři; Male; Female